Main factors that control roadway damage when a steeply dipping coal seam crosses a fault - Hongwei Wang; Jianqiang Jiao; Yongping Wu; Yuanyang Song; Panshi Xie; Shenghu Luo (Geomatics, Natural Hazards & Risk)
When the working face of a steeply dipping coal seam crosses a fault, the dynamic disturbance caused by the mining load induces fault activation, causing large deformation and failure of the roadway. In this study, a physical similarity simulation and numerical calculation method were used to determine the main factors that the deformation and failure of fault zone roadway and reveal the underlying mechanisms. The results show that when crosses a fault, the high static load formed by the coupling of mining stress and fault pillar stress induces mining stress-type fault activation, which leads to large deformation and damage to the roadway in the fault zone. The main controlling factors are the fault location and mining load intensity. In terms of fault location, the vertical stress concentration away from the roadway side of the fault surface was high, the principal stress deflection angle was large, and the surface deformation of the fault on the roadway left side was the greatest. In terms of mining load intensity, the deflection angle of the principal stress of the surrounding rock initially increased and then decreased, and tensile failure easily occurred near the fault surface. These results provide a reference for roadway support.